A8.36 Activated human B cells induce an inflammatory phenotype in synovial fibroblasts. (31st January 2014) - Tretter, Theresa; Stoerch, Hannah; Tykocinski, Lars; Moradi, Babak; Lorenz, Hanns-Martin
Abstract : Background and Objectives: Synovial fibroblasts (SF) are key players in pathogenesis and progression of rheumatoid arthritis (RA). A cross-talk between immune cells and SF is suggested to contribute to chronification of the disease. RA-SF can be found in close proximity to B cells in vivo, with activated proliferating B cells often organised in germinal center- like pseudofollicles. While various reports deal with the influence of SF on B cells, our intention was to clarify the potential influence of B cells on SF Materials and Methods: Highly purified CD19 + B-cells were separated from PBMC by magnetic cell sorting. B-cells were polyclonaly stimulated by BCR-cross-linking with anti-IgM/IgG Antibody or SAC (Staphylococcus aureus Cowan I antigen) and cocultured with SF, that were isolated from synovial biopsies of patients with osteoarthritis (OA-SF). After 48-72h cytokine production was determined by ELISA of cell culture supernatants and phenotypical changes in both cell populations were determined by flow cytometry Results: SF and B cells cultured alone produced low amounts of IL-6 and IL-8. However, in B-SF cocultures the concentrations of both cytokines increased up to 100-fold suggesting that the observed values not just reflect additive but rather synergistic effects. Intracellular staining with fluorochrome-labelled anti-cytokine Abs revealed that the increased cytokine concentrations originated from SF. In contrast, B cell specific production of TNF-alpha and IL-1-beta decreased in cocultures with SF by more than 50%, suggesting an inhibitory feedback mechanism by activated SF towards the B cells. Of note, after removal of B cells SF-specific cytokine production remained constantly increased for several days. Separation of B cells from SFs by semipermeable cell culture inserts (transwell) did not abolish observed effects, suggesting that soluble factors were the main mediators. Addition of neutralizing Abs against TNF-alpha and IL-1-beta to the cocultures significantly reduced SF activation. All effects proved to be stable with little variation between individual donors, different B cell: SF ratios, cell culture media or B cell stimuli used. In addition to IL-6 and IL-8, the production of Matrix-Metalloproteinase-3 (MMP-3) increased in coculture with B cells as well, suggesting that OA-SF developed potentially tissue destructive properties. Conclusions: Activated B cells interact with SF in a reciprocal crosstalk resulting in conversion of OA-SF into SF with an inflammatory phenotype. This process is mediated by B cell derived TNF-alpha, IL-1 beta and other yet to be identified soluble factors.